Current status of virtual reality researches at healthcare: thematic and bibliometric analysis - Kafes, Mustafa; Ileri, Yusuf Yalcin (Frontiers in Virtual Reality, 2025)
IntroductionVirtual reality (VR) technology in the health field is used in processes such as rehabilitative services and therapy for patients, as well as increasing the training and capabilities of the workforce (doctors, nurses, etc.), which is an important factor in the provision of services.MethodsThis study combines quantitative and qualitative methods for a macro overview of the use of VR technology in healthcare. The database -Web of Science (WoS)- search for this study, in which bibliometric analysis was performed, was conducted in September 2023.ResultsA seven-stage structuring strategy was followed for the study findings. This allowed the analyses to be interpreted both independently of each other and in combination with different combinations. While most of the sub-information required for analysis through WoS is at an excellent or near-perfect level (15/16), one of the sub-information (1/16) is at an acceptable level. Although the first publication on the subject was published in 1998, researchers have frequently preferred it as a field of study since 2016. In Bradford’s Law, the number of publications in journals in Zone 1 corresponds to one-third of the total number of publications. In addition, the ratio of the number of publications of the 25 most influential authors in the field to the total number of author publications is similar. The year 2016 is a turning point for this issue. Since this year, the number of publications has increased significantly and the fields of study have started to evolve. Until 2016, simulation-oriented studies generally focused on simulations, and after this date, simulations have evolved into topics that directly affect human life, such as medical education, rehabilitation, therapy, or improvement of behavioral conditions.DiscussionResearch on the use of VR technology in healthcare has had strong growth in recent years. The existing contexts and possibilities underline that this field has the potential to attract more attention in the near future. Cross-sectional methods for implementation and simple ways to integrate VR into existing systems can be seen as what makes the technology so interesting and worthy of research. However, VR in healthcare also has some barriers, such as motion sickness, loss of sense of presence, eye strain, or inappropriate reactions in the real world.